2013
DOI: 10.1097/brs.0b013e3182a7f2c3
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Natural History of Cervical Spondylotic Myelopathy

Abstract: Strong. SUMMARY STATEMENTS: Chronic compression of the spinal cord results in progressive neural cell loss related to secondary mechanisms including apoptosis, neuroinflammation, and vascular disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
260
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 351 publications
(267 citation statements)
references
References 40 publications
1
260
0
6
Order By: Relevance
“…In a systematic review on the natural course of CSM, Karadimas et al reported that 20%-62% of patients will deteriorate neurologically at 3-6 years without surgical intervention. 15 Their review underscores the uncertainty of widely varied clinical presentation of CSM and the clinical dilemma that roughly half of patients may live with CSM without surgical treatment. The choice of optimal treatments and the timing of any intervention remain controversial and reflect a lack of reliable clinical and radiographical factors to predict patients who will experience deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review on the natural course of CSM, Karadimas et al reported that 20%-62% of patients will deteriorate neurologically at 3-6 years without surgical intervention. 15 Their review underscores the uncertainty of widely varied clinical presentation of CSM and the clinical dilemma that roughly half of patients may live with CSM without surgical treatment. The choice of optimal treatments and the timing of any intervention remain controversial and reflect a lack of reliable clinical and radiographical factors to predict patients who will experience deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical factors are classified further into static and dynamic mechanical factors [1][2][3][4][5][6].…”
Section: Cervical Spondylotic Myelopathymentioning
confidence: 99%
“…, 1, 2 CSM in dogs shares similarities with cervical spondylotic myelopathy, the most common cause of chronic compressive cervical myelopathy in people 2, 3, 4. While surgical treatment can attenuate the progression of this human disease, many patients are left with substantial neurologic disability 3.…”
mentioning
confidence: 99%
“…Gaps in the knowledge of the disease pathobiology have historically limited therapeutic advances in this human condition and current studies are actively investigating the disease pathogenesis with the objective of developing new neuroprotective approaches to improve outcome 3, 4, 5, 6, 7, 8, 9. Rodent models of cervical spondylotic myelopathy show that neuronal and oligodendrocyte apoptosis, chronic neuroinflammation, and microvascular compromise result in progressive neural degeneration and potentially irreversible spinal cord (SC) damage and could be related to treatment failure, poor long‐term outcome, or both 3, 4, 5, 6, 7, 8, 9. Similar changes have been observed in the SC of CSM‐affected dogs 2.…”
mentioning
confidence: 99%